A hyaluronic acid composite gel for tear trough filling and preparation method thereof

A hyaluronic acid composite for tear trough filling was prepared by mixing medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen in phosphate buffer and subjecting them to vacuum degassing and physical cross-linking. The gel solves the problems of difficulty in injection, short maintenance time of effect, and affected safety in the existing technology, and achieves a filling effect that is easy to inject, has long maintenance time, and has high safety.

CN114874468BActive Publication Date: 2025-01-24HYAMED BIOTECHNOLOGY (ZHUHAI) CO LTD

Patent Information

Application Number
CN202210562026.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-23
Publication Date
2025-01-24
Estimated Expiration
2042-05-23

AI Technical Summary

Technical Problem

The existing sodium hyaluronate gels used for tear trough filling have problems such as difficulty in injection, short maintenance time and safety. In particular, crosslinked sodium hyaluronate gels have high requirements during injection and have a Tindal effect. The continuous effect of sodium hyaluronate composite solution is not good.

Method used

A composite gel of medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen is mixed with phosphate buffer and degassed by vacuum stirring, followed by a physical cross-linking process of rapid heating-insulation-rapid cooling. , avoid using cross-linking agents.

Benefits of technology

It achieves the filling effect that is convenient for injection, long -lasting time, and high safety, avoids the appearance of Dadar effects, and has the function of repairing and supplementing skin nutrition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114874468B_ABST
    Figure CN114874468B_ABST
Patent Text Reader

Abstract

The present invention provides a hyaluronic acid composite gel for tear groove filling and a preparation process thereof, wherein the composite gel is cross-linked by medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen, wherein the mass percentage of medium molecular weight sodium hyaluronate and low molecular weight sodium hyaluronate in the composite gel is 1.2-2.0%, the mass percentage of recombinant collagen in the composite gel is 0.4-0.7%, and the remainder of the composite gel is phosphate buffer. The preparation method is cross-linked by physical means of rapid heating-insulation-rapid cooling. The composite gel of the present invention, through the coordination of medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen, can prolong the duration of the filling effect while ensuring the filling effect, effectively avoid the occurrence of the Tyndall effect, have high safety, and can also repair and supplement skin nutrition; no cross-linking agent is required, and there is no residual risk.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a method for preparing a hyaluronic acid composite gel and the prepared hyaluronic acid composite gel. Background Art

[0002] With the improvement of living standards, people's pursuit of "beauty" has gradually increased, and filling products for facial and neck wrinkles have become the darling of the market. At present, the products used for tear trough filling and repair on the market mainly include cross-linked sodium hyaluronate gel and sodium hyaluronate composite solution containing nutrients such as amino acids. Among them, cross-linked sodium hyaluronate gel has certain risks in tear trough filling. Due to the thin skin at the injection site, the doctor's injection technique is very high. The injection doctor is not sure about the injection depth, angle, strength, dosage and injection method, or the anatomical structure of the tear trough is not clear, which will lead to poor injection effect. If the injection is too shallow, the tear trough may turn blue and there will be a raised Tyndall effect at the tear trough. If the injection is too deep, the tear trough cannot be supported and the effect is not good. The sodium hyaluronate composite solution has a lower risk, but the selected sodium hyaluronate has a low molecular weight, the sodium hyaluronate content in the solution is low, and the sodium hyaluronate exists in a free form. Therefore, it only has a good immediate effect and nutritional supplement effect during injection, and the sustained effect is poor, and it is degraded within a few days. In addition, chemical cross-linking is often used in the gel preparation process, and the residue of chemical cross-linking agents will affect the safety of the gel.

[0003] Chinese patent CN110016152A provides a method for preparing sodium hyaluronate gel for cross-linking filling, which dissolves sodium hyaluronate gel in sodium hydroxide solution, then adds cross-linking agent 1,4-butanediol diglycidyl ether for cross-linking reaction, then swells the obtained sodium hyaluronate gel, dehydrates it in an organic solvent, and repeats several times to remove the cross-linking agent. The preparation process of this patent is complicated, and an additional step is required to remove the cross-linking agent. The molecular weight of hyaluronic acid is not specified, and there are inevitably problems such as difficulty in injection and rapid metabolism.

[0004] Therefore, developing a tear trough filling gel that is easy to inject, has a long maintenance time, and is highly safe is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] In view of this, the present invention provides a hyaluronic acid composite gel and a preparation method thereof.

[0006] The technical solution of the present invention is as follows:

[0007] A hyaluronic acid composite gel for tear trough filling, wherein the hyaluronic acid composite gel is prepared by cross-linking medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen;

[0008] The mass percentage of medium molecular weight sodium hyaluronate and low molecular weight sodium hyaluronate in the composite gel is 1.2-2.0%; the mass percentage of recombinant collagen in the composite gel is 0.4-0.7%; and the remainder of the composite gel is phosphate buffer.

[0009] Furthermore, in the above-mentioned hyaluronic acid composite gel, the mass ratio of medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen in the composite gel is 3:3:1.

[0010] Furthermore, in the above-mentioned hyaluronic acid composite gel, the mass percentage of medium molecular weight sodium hyaluronate and low molecular weight sodium hyaluronate in the composite gel is 1.6%; the mass percentage of recombinant collagen in the composite gel is 0.5%; and the remainder of the composite gel is phosphate buffer.

[0011] Furthermore, in the above-mentioned hyaluronic acid composite gel, the molecular weight of the medium molecular weight sodium hyaluronate is 1000-1300 kDa, the molecular weight of the low molecular weight sodium hyaluronate is 200-500 kDa, and the molecular weight of the recombinant collagen is 40-60 kDa.

[0012] The present invention also provides a method for preparing the above hyaluronic acid composite gel, comprising the following steps:

[0013] S1. Mix and disperse medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen in phosphate buffer, stir the mixture, and adjust the pH of the mixture to form a homogeneous viscous solution;

[0014] S2. Degas the viscous solution obtained in S1 by vacuum stirring until there are no obvious bubbles in the viscous solution, and fill it into a prefilled syringe;

[0015] S3. Perform a rapid heating-keeping-rapid cooling operation on the prefilled syringe obtained in S2 to cross-link the medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen.

[0016] Furthermore, in the above-mentioned preparation method, S1 is carried out at 20-35° C., and the pH of the obtained viscous solution is adjusted to 6-8.

[0017] Furthermore, in the above preparation method, the pH adjustment step in S1 is as follows:

[0018] Measure the pH of the mixed solution;

[0019] If the pH is less than 6, add 0.1 mol / L sodium hydroxide solution to the mixed solution until the pH of the mixed solution is ≥ 6;

[0020] If pH>8, add 0.1mol / L hydrochloric acid solution to the mixture until the pH of the mixture is ≤8.

[0021] Furthermore, in the above preparation method, during the vacuum stirring and degassing in S2, the vacuum degree of the vacuum stirrer is ≤-900 mbar, and the degassing is stirred at a speed of 20 rpm for 30-50 minutes.

[0022] Furthermore, in the above-mentioned preparation method, the S3 rapid heating-heat preservation-rapid cooling steps are as follows:

[0023] The steam-air mixed gas medium is heated, pressurized and heated, so that the pre-filled syringe obtained in S3 is heated to 110-130° C. within 10 minutes;

[0024] The prefilled syringe is kept warm in the gas medium for 5-10 minutes;

[0025] After the insulation is completed, spray chilled water on the pre-filled syringe to cool it down to 20-35℃ within 10 minutes.

[0026] The beneficial effects of the present invention are as follows: the hyaluronic acid composite gel of the present invention can extend the duration of the filling effect while ensuring the filling effect through the combination of medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen, effectively avoid the occurrence of the Tyndall effect, have high safety, and can also repair and supplement skin nutrition. The preparation method of the hyaluronic acid composite gel of the present invention cross-links the components through the physical means of rapid heating-heat preservation-rapid cooling, does not require a cross-linking agent, and has no residual risk. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can derive other drawings based on the following drawings without creative work.

[0028] Figure 1 is a state diagram of the hyaluronic acid composite gels prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention being placed on a plastic plate;

[0029] Figure 2 It is a state diagram of the hyaluronic acid composite gel prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention on a plastic plate inclined at 30 degrees. DETAILED DESCRIPTION

[0030] The experimental methods used in the following examples are all conventional methods unless otherwise specified; the reagents, materials, etc. used in the following examples are all commercially available products, or can be prepared by known methods unless otherwise specified. The medium molecular weight sodium hyaluronate and low molecular weight sodium hyaluronate used in the following examples were purchased from Huaxi Biotechnology Co., Ltd.; recombinant collagen was purchased from Jiangsu Jiangshan Juyuan Biotechnology Co., Ltd. The experimental methods in the following examples where specific conditions are not specified are usually carried out according to conventional conditions such as those described in Sambrook et al., Molecular Cloning: A Laboratory Manual (New York: Cold Spring Harbor Laboratory Press, 1989), or according to the conditions recommended by the manufacturer.

[0031] Example 1

[0032] Take 0.16g of sodium hyaluronate with a molecular weight of 1200kDa, 0.16g of sodium hyaluronate with a molecular weight of 250kDa and 0.05g of recombinant collagen with a molecular weight of 50kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 5.5, add 0.1mol / L sodium hydroxide solution to adjust the pH value of the mixed solution to 7, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -1000mbar and a speed of 20rpm for 40 minutes. After degassing to obtain a bubble-free viscous solution, the degassed viscous solution is filled into a prefilled syringe under negative pressure and aseptic conditions, and the steam-air mixed medium is heated at 110kPa to make the filled prefilled syringe reach 125°C within 8 minutes, keep warm for 8min, and then spray chilled water on the prefilled syringe to reduce it to 25°C within 10 minutes.

[0033] Example 2

[0034] Take 0.2g of sodium hyaluronate with a molecular weight of 1300kDa, 0.2g of sodium hyaluronate with a molecular weight of 500kDa and 0.07g of recombinant collagen with a molecular weight of 60kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 8.2, add 0.1mol / L hydrochloric acid solution to adjust the pH value of the mixed solution to 8, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -1200mbar and a speed of 20rpm for 50 minutes. After degassing to obtain a bubble-free viscous solution, the degassed viscous solution is filled into a prefilled syringe under negative pressure and aseptic conditions, and the steam-air mixed medium is heated at 110kPa to make the filled prefilled syringe reach 130°C within 10 minutes, keep warm for 10min, and then spray chilled water on the prefilled syringe to reduce it to 25°C within 10 minutes.

[0035] Example 3

[0036] Take 0.12g of sodium hyaluronate with a molecular weight of 1000kDa, 0.12g of sodium hyaluronate with a molecular weight of 200kDa and 0.04g of recombinant collagen with a molecular weight of 40kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 5.2, add 0.1mol / L sodium hydroxide solution to adjust the pH value of the mixed solution to 6, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -900mbar and a speed of 20rpm for 30 minutes. After degassing to obtain a bubble-free viscous solution, the degassed viscous solution is filled into a prefilled syringe under negative pressure and aseptic conditions, and the steam-air mixed medium is heated at 110kPa to make the filled prefilled syringe reach 110°C within 5 minutes, keep warm for 5min, and then spray chilled water on the prefilled syringe to reduce it to 25°C within 10 minutes.

[0037] Comparative Example 1

[0038] Take 0.32g of sodium hyaluronate with a molecular weight of 1200kDa and 0.06g of recombinant collagen with a molecular weight of 50kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 5.7, add 0.1mol / L sodium hydroxide solution to adjust the pH value of the mixed solution to 7, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -1000mbar and a rotation speed of 20rpm for 40 minutes. After degassing to obtain a bubble-free viscous solution, the degassed viscous solution is filled into a prefilled syringe under negative pressure and aseptic conditions, and the steam-air mixed medium is heated at 110kPa to make the filled prefilled syringe reach 125°C within 8 minutes, keep warm for 8min, and then spray chilled water on the prefilled syringe to reduce it to 25°C within 10 minutes.

[0039] Comparative Example 2

[0040] Take 0.5 g of sodium hyaluronate with a molecular weight of 1200 kDa, 0.5 g of sodium hyaluronate with a molecular weight of 250 kDa and 0.15 g of recombinant collagen with a molecular weight of 50 kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10 g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 8.2, add 0.1 mol / L hydrochloric acid to adjust the pH value of the mixed solution to 7, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -1000 mbar and a rotation speed of 20 rpm for 40 minutes. After degassing to obtain a bubble-free viscous solution, the degassed viscous solution is filled into a prefilled syringe under negative pressure and aseptic conditions, and the steam-air mixed medium is heated at 110 kPa to make the filled prefilled syringe reach 125° C. within 8 minutes, keep warm for 8 minutes, and then spray chilled water on the prefilled syringe to reduce it to 25° C. within 10 minutes.

[0041] Comparative Example 3

[0042] Take 0.32g of sodium hyaluronate with a molecular weight of 250kDa and 0.06g of recombinant collagen with a molecular weight of 50kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 5.6, add 0.1mol / L sodium hydroxide solution to adjust the pH value of the mixed solution to 7, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -1000mbar and a rotation speed of 20rpm for 40 minutes. After degassing to obtain a bubble-free viscous solution, the degassed viscous solution is filled into a prefilled syringe under negative pressure and aseptic conditions, and the steam-air mixed medium is heated at 110kPa to make the filled prefilled syringe reach 125°C within 8 minutes, keep warm for 8min, and then spray chilled water on the prefilled syringe to reduce it to 25°C within 10 minutes.

[0043] Comparative Example 4

[0044] Take 0.1 g of sodium hyaluronate with a molecular weight of 1200 kDa, 0.1 g of sodium hyaluronate with a molecular weight of 250 kDa and 0.03 g of recombinant collagen with a molecular weight of 50 kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10 g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 8.4, add 0.1 mol / L hydrochloric acid to adjust the pH value of the mixed solution to 7, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -1000 mbar and a rotation speed of 20 rpm for 40 minutes. After degassing to obtain a bubble-free viscous solution, the degassed viscous solution is filled into a prefilled syringe under negative pressure and aseptic conditions, and the steam-air mixed medium is heated at 110 kPa to make the filled prefilled syringe reach 125° C. within 8 minutes, keep warm for 8 minutes, and then spray chilled water on the prefilled syringe to reduce it to 25° C. within 10 minutes.

[0045] Comparative Example 5

[0046] Take 0.16g of sodium hyaluronate with a molecular weight of 1200kDa, 0.16g of sodium hyaluronate with a molecular weight of 250kDa and 0.05g of recombinant collagen with a molecular weight of 50kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 5.7, add 0.1mol / L sodium hydroxide solution to adjust the pH value of the mixed solution to 7, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -1000mbar and a speed of 20rpm. Stir for 40 minutes, degas to obtain a bubble-free viscous solution, and then fill the degassed viscous solution into a prefilled syringe under negative pressure and aseptic conditions, heat the steam-air mixed medium at 110kPa, so that the filled prefilled syringe reaches 100°C within 8 minutes, keep warm for 8min, and then spray chilled water on the prefilled syringe to reduce it to 25°C within 10 minutes.

[0047] Comparative Example 6

[0048] Take 0.16g of sodium hyaluronate with a molecular weight of 1200kDa, 0.16g of sodium hyaluronate with a molecular weight of 250kDa and 0.05g of recombinant collagen with a molecular weight of 50kDa, mix and disperse them in phosphate buffered saline (PBS) to a total weight of 10g, stir and dissolve, and at the same time measure the pH value of the mixed solution to 5.7, add 0.1mol / L sodium hydroxide solution to adjust the pH value of the mixed solution to 7, fully dissolve and evenly obtain a clear homogeneous viscous solution, and then stir and degas in a vacuum mixer with a vacuum degree of -1000mbar and a speed of 20rpm for 40 minutes. After degassing to obtain a bubble-free viscous solution, the degassed viscous solution is filled into a prefilled syringe under negative pressure and aseptic conditions, and the steam-air mixed medium is heated at 110kPa to make the filled prefilled syringe reach 125°C within 8 minutes, keep warm for 3min, and then spray chilled water on the prefilled syringe to reduce it to 25°C within 10 minutes.

[0049] Performance Testing

[0050] (1) Appearance

[0051] The hyaluronic acid composite gels prepared in Examples 1-3 and Comparative Examples 1-4 were placed on a plastic plate at room temperature. Figure 1 ; After tilting the plastic plate 30°, the state is as follows Figure 2 .

[0052] Table 1 Preparation process of each sample

[0053]

[0054]

[0055] like Figure 1 , Figure 2 As shown, when the hyaluronic acid composite gels prepared in each embodiment and comparative example are placed on a plastic plate, their appearance and properties are similar, and they are all transparent droplets; after the plastic plate is tilted 30°, the hyaluronic acid composite gels prepared in comparative examples 3 and 4 flow downward, and the fluidity of the hyaluronic acid composite gel prepared in comparative example 4 is greater than that of comparative example 3; the hyaluronic acid composite gel prepared in embodiment 3 also has a certain flow, but the fluidity is less than that of comparative examples 3 and 4; the hyaluronic acid composite gels obtained by the other preparation methods do not flow. Comparative examples 5 and 6 (not shown in the figure) also flow on a plastic plate tilted at 30°, and the degree of flow is similar to that of comparative example 4.

[0056] (2) Shear viscosity

[0057] At 25 °C, a rotational rheometer was used to measure the shear rate from 0.001 s -1 ~1000s -1 Flow scan was performed under the condition of 2.5 s. -1 The shear viscosity corresponding to the shear rate is compared.

[0058] Table 2 Gel shear viscosity obtained by different preparation processes

[0059]

[0060]

[0061] Shear viscosity reflects the viscosity of the fluid. The shear viscosity of Examples 1-3 and Comparative Examples 1-2 is greater than 30, while the shear viscosity of Comparative Examples 3-6 is less than 20. The above appearance and shear viscosity test results show that, compared with Examples 1-3 and Comparative Examples 1 and 2, Comparative Examples 3-6 are more likely to move and be absorbed after injection, and cannot meet the requirements of maintaining a long-term filling effect.

[0062] (3) Elastic modulus

[0063] At 25°C, an oscillation test was performed using a rotational rheometer at a strain of 5%, and the elastic modulus value corresponding to a frequency of 1 Hz was taken for comparison.

[0064] Table 3 Elastic modulus of gels obtained by different preparation processes

[0065]

[0066]

[0067] The elastic modulus is an indicator of the ease with which a material can produce elastic deformation. The larger the value, the greater the stiffness of the material. For gels, the greater the stiffness, the more difficult it is to degrade. The elastic modulus of Examples 1-3 and Comparative Examples 3-6 is less than 140Pa, while the elastic modulus of Comparative Examples 1 and 2 exceeds 250Pa. The above test results show that, compared with other preparation processes, the gels prepared by Comparative Examples 1 and 2 are prone to adverse reactions such as hard touch, Tyndall effect, and difficulty in degradation during use.

[0068] (4) Pushing force

[0069] Take the prepared hyaluronic acid composite gel, push the syringe push rod at a constant speed, the syringe needle is 27G, the pushing speed is 30mm / min, and detect the pushing force.

[0070] Table 4 Gel pushing force obtained by different preparation processes

[0071] Preparation process Pushing force(N) Comparative Example 1 18.41 Comparative Example 2 17.23 Example 1 10.09 Example 2 12.87 Example 3 8.21 Comparative Example 3 6.65 Comparative Example 4 2.68 Comparative Example 5 4.56 Comparative Example 6 3.47

[0072] The push force requirement for surgical hand suitability is <15 N. The push forces of Examples 1-3 and Comparative Examples 3-6 are all less than 15 N, while the push forces of Comparative Examples 1 and 2 are both greater than 16 N. The above results show that the push force of the gels prepared in Comparative Examples 1 and 2 is too large and does not meet the surgical hand suitability requirement.

[0073] (5) In vivo experiments

[0074] The hyaluronic acid composite gel prepared by the preparation methods of the embodiment and the comparative example was injected into seven-week-old male nude mice, and the appearance of the injection site was observed. The mice were killed 60 days after the injection, the skin at the injection site was cut open, the remaining gel was extracted, and the percentage of the remaining gel was measured by weighing.

[0075] Table 5 In vivo experimental results of gels obtained by different preparation processes

[0076]

[0077] On the day of injection, the injection sites of mice in each group had similar appearances, all with soybean-sized protrusions; within one week after injection, the subcutaneous protrusions of mice in groups 3-6 of the comparative examples disappeared, and they were smooth to the touch without a sense of protrusion. The subcutaneous protrusions of mice in groups 1-2 of the comparative examples and groups 1-3 of the examples shrank to varying degrees. When the protrusions were touched, the protrusions of mice in groups 1-2 of the comparative examples felt harder, while the protrusions of mice in groups 1-3 of the examples felt softer and more natural. The above phenomenon shows that compared with the comparative example, the gel filling effect obtained in examples 1-3 is better.

[0078] Although the embodiments of the present application have been shown and described above, it is understood that the above embodiments are exemplary and cannot be construed as limitations on the present application. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A hyaluronic acid composite gel for tear trough filling, wherein the hyaluronic acid composite gel is prepared by cross-linking medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen, characterized in that: The mass percentages of the medium molecular weight sodium hyaluronate and the low molecular weight sodium hyaluronate in the composite gel are both 1.2-2.0%; The mass percentage of the recombinant collagen in the composite gel is 0.4-0.7%; The remainder of the composite gel is phosphate buffer; The molecular weight of the medium molecular weight sodium hyaluronate is 1000-1300 kDa, the molecular weight of the low molecular weight sodium hyaluronate is 200-500 kDa, and the molecular weight of the recombinant collagen is 40-60 kDa.

2. The hyaluronic acid composite gel according to claim 1, characterized in that The mass ratio of the medium molecular weight sodium hyaluronate, the low molecular weight sodium hyaluronate and the recombinant collagen in the composite gel is 3:3:

1.

3. The hyaluronic acid composite gel according to claim 1, characterized in that The mass percentages of the medium molecular weight sodium hyaluronate and the low molecular weight sodium hyaluronate in the composite gel are both 1.6%; The mass percentage of the recombinant collagen in the composite gel is 0.5%; The remainder of the composite gel is phosphate buffer.

4. A method for preparing the hyaluronic acid composite gel for tear trough filling according to claim 1, comprising the following steps: S1. Mix and disperse medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen in phosphate buffer, stir the mixture, and adjust the pH of the mixture to form a homogeneous viscous solution; S2. Degas the viscous solution obtained in S1 by vacuum stirring until there are no obvious bubbles in the viscous solution, and fill it into a prefilled syringe; S3. Perform a rapid heating-keeping-rapid cooling operation on the prefilled syringe obtained in S2 to cross-link the medium molecular weight sodium hyaluronate, low molecular weight sodium hyaluronate and recombinant collagen.

5. The preparation method according to claim 4, characterized in that: S1 is carried out at 20-35°C, and the pH of the resulting viscous solution is 6-8 after pH adjustment.

6. The preparation method according to claim 4 or 5, characterized in that: The steps for adjusting pH in S1 are as follows: Measure the pH of the mixed solution; If the pH is less than 6, add 0.1 mol / L sodium hydroxide solution to the mixed solution until the pH of the mixed solution is ≥ 6; If pH>8, add 0.1mol / L hydrochloric acid solution to the mixture until pH of the mixture is ≤8.

7. The preparation method according to claim 4, characterized in that: When S2 is vacuum-stirring and degassing, the vacuum degree of the vacuum stirrer is ≤-900mbar, the speed is 20rpm, and the degassing is continued for 30-50 minutes.

8. The preparation method according to claim 4, characterized in that: The steps of S3 rapid heating-heat preservation-rapid cooling are as follows: Pressurize and heat the steam-air mixed gas medium so that the pre-filled syringe obtained in S3 is heated to 110-130° C. within 10 minutes; The prefilled syringe is kept warm in the gas medium for 5-10 minutes; After the heat preservation is completed, the prefilled syringe is sprayed with chilled water to cool the prefilled syringe to 20-35° C. within 10 minutes.

Citation Information

Patent Citations

  • Preparation method for cross-linked sodium hyaluronate gel used for filling

    CN110016152A

  • Hybrid cooperative complexes of hyaluronic acid

    CN103119068A

  • Medicine composition for water-optical treatment and application of medicine composition

    CN105233270A

Cited By

  • Hyaluronic acid-collagen composite gel for face filling and preparation method of hyaluronic acid-collagen composite gel

    CN122499364A